Penegakan Hukum Pidana Terkait Penyidikan Tindak Pidana Narkotika Dalam Perspektif Undang Undang Nomor 35 Tahun 2009 Tentang Narkotika(Studi Kasus di Kepolisian Resort Aceh Tengah) - Kadir, Hardi Meladi (Universitas Islam Sumatera Utara, 2022)
The enforcement of criminal law in the process of investigating narcotics users as perpetrators of narcotics crimes at the Central Aceh Police starts from receiving reports, taking the first action, arrests, searches, confiscates, examines suspects and witnesses, detention, and transfers case files and suspects to the prosecutor's office. .The entire investigation process that has been carried out by the Polri investigators will then be continued by the prosecutor's office in terms of preparing the prosecution to be submitted in a court trial and subsequently the sentencing of the defendant, all of which takes place in a Criminal Justice System in the context of enforcing criminal law.The obstacles faced by the Narcotics Satres of the Central Aceh Police in conducting investigations against narcotics crimes are limited personnel, budget, and the ability of investigators of the Narcotics Satres of the Central Aceh Police to conduct investigations and investigations of narcotics crimes. Not to mention the ability of investigators to conduct investigations into narcotics trafficking.It is recommended that the investigations and investigations carried out by the Narcotics Satres of the Central Aceh Police are supported in terms of personnel, budget, and increasing the capacity of investigators by the Aceh Police by adding personnel, increasing the budget, and increasing the ability of investigators. Keywords: Crime, Drugs